Green Synthesis of AuNPs by Acinetobacter sp. GWRVA25: Optimization, Characterization, and Its Antioxidant Activity - Nadhe, Shradhda B.; Wadhwani, Sweety A.; Singh, Richa; Chopade, Balu A. (Frontiers in Chemistry, 2020)
Bacteriogenic synthesis of metal nanoparticles is ecofriendly and greatly influenced by physico-chemical reaction parameters with respect to shape and size. Thus, present work aimed to synthesize and optimization of bacteriogenic gold nanoparticles (AuNPs) and study their antioxidant activity. Acinetobacter sp. cells were able to synthesize AuNPs, when challenged with tetra-chloroauric acid (HAuCl4). By physicochemical optimization, maximum synthesis was obtained with 72 h old culture using 2.1×109 CFU/ml cell density. Whereas, pH-7 is suitable for AuNPs synthesis. HAuCl4 concentration (0.5 mM) enhanced the formation of monodispersed and spherical nanoparticles (15 ± 10 nm). At 37°C temperature, Acinetobacter sp. released nanoparticles in supernatant. From characterization, AuNPs were found to be crystalline in nature with negative surface charge. AuNPs showed up to 86% different radical scavenging ability, exhibiting antioxidant activity. In conclusion, spherical AuNPs can be synthesized using Acinetobacter sp. through physicochemical optimization. This is the first report of antioxidant activity exhibited by monodispersed bacteriogenic AuNPs synthesized using Acinetobacter sp.